Life-span differences in the uses and gratifications of tablets: Implications for older adults. (November 2015) - Magsamen-Conrad, Kate; Dowd, John; Abuljadail, Mohammad; Alsulaiman, Saud; Shareefi, Adnan
Highlights: Tablet uses: information seeking, relationship maintenance, style, amusement, & organization. There are life-span differences in tablet uses and gratifications. Tablet uses and gratifications predict hours of tablet use across four generations. Life-span tablet use disparities have practical applications, especially for health management. Abstract: This study extends Uses and Gratifications theory by examining the uses and gratifications of a new technological device, the tablet computer, and investigating the differential uses and gratifications of tablet computers across the life-span. First, we utilized a six-week tablet training intervention to adapt and extend existing measures to the tablet as a technological device. Next, we used paper-based and online surveys ( N = 847), we confirmed four main uses of tablets: (1) information seeking, (2) relationship maintenance, (3) style, (4) amusement and killing time, and added one additional use category (5) organization. We discovered differences among the five main uses of tablets across the life-span, with older adults using tablets the least overall. Builders, Boomers, GenX and GenY all reported the highest means for information seeking. Finally, we used a structural equation model to examine how uses and gratifications predicts hours of tablet use. The study provides limitations and suggestions for future research and marketers. In particular, this study offers insight to the relevancy of theory as it applies to particular information and communication technologies and consideration of how different periods in the life-span affect tablet motivations.